2016
DOI: 10.1108/jcm-04-2015-1390
|View full text |Cite
|
Sign up to set email alerts
|

Influences of customer participation and customer brand engagement on brand loyalty

Abstract: Purpose Value co-creation assumes that customers take active roles and create value together with firms. This paper aims to investigate the short- and long-term effects of customer participation on brand loyalty, through brand satisfaction. Participation effects were also examined among social media-using customers with the additional explanatory factor of brand engagement. Design/methodology/approach Two studies were conducted among insurance customers: a cross-sectional study using a nationwide sample (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(39 citation statements)
references
References 80 publications
1
34
0
4
Order By: Relevance
“…From the marketing perspective, companies use consumer participation as an effective strategic tool to drive positive consumer responses. Prior research demonstrates that companies can enhance satisfaction, trust, and loyalty by engaging consumers in production process [4,22,26]. In addition, consumer participation in CSR can lead to more positive responses by increasing their identification with the CSR activities compared to general CSR activities [5,27].…”
Section: Consumer Participation In Corporate Social Responsibility (Csr)mentioning
confidence: 99%
See 1 more Smart Citation
“…From the marketing perspective, companies use consumer participation as an effective strategic tool to drive positive consumer responses. Prior research demonstrates that companies can enhance satisfaction, trust, and loyalty by engaging consumers in production process [4,22,26]. In addition, consumer participation in CSR can lead to more positive responses by increasing their identification with the CSR activities compared to general CSR activities [5,27].…”
Section: Consumer Participation In Corporate Social Responsibility (Csr)mentioning
confidence: 99%
“…Participation effort refers to the degree to which consumers put efforts and resources into a production process [26]. Following prior works, we define participation effort as the degree of effort and resource input required from consumers to participate in companies' CSR activities.…”
Section: Level Of Participation Effortmentioning
confidence: 99%
“…Value co-creation has a strong focus on the roles of customers as active participants in the value creation process, and consider them resource integrators (Prahalad & Ramaswamy, 2004;Vargo & Lusch, 2004). Customer participation in insurance contexts studied through the lens of value co-creation, has been shown to have a short-term positive effect on brand satisfaction and brand loyalty (Apenes Solem, 2016). Leading to positive effects on the motivation on employees, establishing that"... understanding how companies can harness the benefits of customer participation is of great importance."…”
Section: Culture and Customer Participation In Digital Transformationmentioning
confidence: 99%
“…Engaging their customers with their digital strategy may be a good first step towards this objective, as the survey revealed that a significant majority of customers lacked familiarity with the aforementioned strategy. As the value networks of an organization grow increasingly complex during a DT process, adopting agile customer-inclusive practices (Kettunen & Laanti, 2017) and developing ways to sustain the advantages of co-creation (Apenes Solem, 2016) may be critical to the success of a DT process. We believe that the customer perspective is a dimension of DT that stands to benefit the managerial practices and understanding of the field going forward.…”
Section: Customer Participationmentioning
confidence: 99%
“…Behavioural loyalty, however, is a commitment to a service or brand despite the availability of competitive alternatives. [34] Given the local context of healthcare service provision, it is prudent to adopt a working definition of loyalty as a combination of patients' attitude and behaviour that translates into repurchase or regular use of service. Dong et al concluded that customer participation is positively related to service quality and satisfaction but has mixed impacts on future purchase intentions.…”
Section: Patient Loyaltymentioning
confidence: 99%